Risk Factors for Sepsis Following Cesarean Section in Ulaanbaatar: A Case-Control Study - Dagshinjav, Narantsaatsralt; Tudevdorj, Erkhembaatar; Davaasuren, Munkhzul; Gurjav, Naran; Jav, Lkhagvasuren (Central Asian Journal of Medical Sciences, 2017)
Objectives: The aim of this study was to determine the incidence of post-cesarean sepsis in patients undergoing a cesarean section (CS) and to identify risk factors and the impact of antibiotic prophylaxis on this condition. Methods: All cesarean deliveries performed at Ulaanbaatar Urguu Maternity Hospital and National Center for Maternal and Child Health (NCMCH) from October 1st 2013 to October 1st 2015 were evaluated for sepsis, based on criteria established by Centers for Disease Control and Prevention’s National Healthcare Safety Network (CDC/NHSN). Medical records of case study and control patients were reviewed when they had post operation infection and revisited the hospital. Records were also compared to and included sociodemographic and clinical characteristics. Results: Overall findings were: 47.4% (361/ 761) of cases were complicated by wound infection and the control group without wound infections was 52.6% (400/761). Post-cesarean wound infection risk factors were statistically determined by: 1) emergency surgery (95% CI=2.8; P=0.35); 2) Twin pregnancy (95% CI=5.8; P=0.2); 3) Premature rupture of membrane (95% CI=6.4; P=0.26) and; 4) Failed induction (95% CI=4.6; P=0.5). Conclusion: Identifying high-risk patients who will require intensive postoperative care is critical in reducing incidences of post-cesarean wound infection.